Internal Control System for the Management of Petty Cash Funds at the UPT Office of Labor Supervision Region I, North Sumatra Province - Hikmatul Fadilah; Rahmat Daim Harahap (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This writing is entitled